2005
DOI: 10.1093/geront/45.6.828
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Design and Program to Train Older Adults to Use Personal Digital Assistants

Abstract: The PDA, supported with well-designed software and well-executed training, can provide unique benefits to older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Moreover, the feeling of constantly lagging behind a rapidly improving and changing technological world has been identified as discouraging (e.g. Sterns 2005, Hiemstra 1991). …”
Section: The Risk Of Inadequate Informationmentioning
confidence: 99%
“…Moreover, the feeling of constantly lagging behind a rapidly improving and changing technological world has been identified as discouraging (e.g. Sterns 2005, Hiemstra 1991). …”
Section: The Risk Of Inadequate Informationmentioning
confidence: 99%
“…Previous studies found that differences in experience were an important factor in efficient computer interaction (Birdi et al, 1997;Sjo¨linder et al, 2005) and that practice by older adults resulted in age-related performance improvements in the use of personal digital assistants (PDAs) (Mayhorn et al, 2005;Sterns, 2005). In addition, computer use and/or training over multiple weeks was found to improve the negative attitudes of older people toward technology (Danowski and Sacks, 1980;Jay and Willis, 1992), and diminish their anxiety levels (Charness et al, 1992).…”
Section: Effect Of Background Knowledge On Age-related Interaction DImentioning
confidence: 99%
“…Vividness of autobiographical memories also declines with age (Nigro & Neisser, 1983) as does prospective memory (Maylor, 1998), which is defined as the memory that enables a person to remember to do something as part of a set of ongoing cognitive tasks. Fortunately, memory aids, such as writing down information (Hartley, 2002) or the innovative use of personal digital assistants (PDAs) with elders (Sterns, 2005), can often ameliorate the impact of some of these changes.…”
Section: The Elder Body and Mindmentioning
confidence: 99%